A STUDY OF LINGUISTIC COMPRESSION IN TRANSLATION FROM ENGLISH TO UZBEK - Usmonjonova, Mahliyo (Журнал иностранных языков и лингвистики, 2023)
This article describes the use of linguistic compression in translation from English to Uzbek